Enhancing Community Knowledge on Proper Drug Storage through Educational Activities at the Griya Hamparan Warga Indah Complex Handil Bakti South Kalimantan - Ahdyani, Risa; Rizqia, Keisya Davina; Arianti, Suci; Muthia, Azizah; Rahmawati, Lili; Rahmansyah, Fadhil Nur (UrbanGreen Central Media, 2025)
Medicines are essential for maintaining and improving public health. People often store medicines at home for ongoing use, future needs, or leftover treatments. However, storage practices frequently ignore proper guidelines, risking decreased drug quality and medication errors. This activity aimed to improve community knowledge at Hamparan Warga Indah Complex on safe drug storage, including expiration and beyond-use dates. Methods included structured interviews with observation and health promotion via direct counseling supported by leaflets and educational videos. Evaluation used pretest and posttest to measure knowledge changes. Results showed significant improvement, with average scores rising from 71.42% to 98.57%. Knowledge increased across all indicators, demonstrating the activity's effectiveness in enhancing community understanding of proper household drug storage. The intervention successfully addressed storage misconceptions and reinforced safe medication management at home, contributing to better public health outcomes through improved individual practices.